Historical Soybean Study: Grain Filling × Nitrogen Fixation - S. Tamagno; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
Genetic gain is characterized by comparing the performance of genotypes from a different year of release. Historic studies are useful to understand changes in yield-related traits that also contribute to yield potential. This study aims to quantify yield improvement for soybean through a set of seven genotypes with different years of release, and their respective numerical components, with a focus on final seed weight generation under two different nitrogen (N) conditions. Changes in biological N fixation (BNF) were quantified during the seed-filling period (SFP). Non-linear models were fit to the data to characterize seed weight and BNF changes throughout the SFP. Genetic gain led to an overall yield increase of 0.49 bu/a/year mainly explained by increases in the seed number rather than seed weight. Nitrogen application increased yield equally across genotypes (P<0.01), and final seed weight in all genotypes tested. Biological nitrogen fixation activity was reduced by 44% at the onset of the SFP, however, no N deficiencies were observed.
Keywords: soybean; BNF; nitrogen; genetic gain; seed weight